EFEKTIVITAS STRATEGI MEDIA SOSIAL DALAM MENINGKATKAN KESADARAN MEREK PRODUK PADA UD. TANDA SETIA KOTA GUNUNGSITOLI - Daswan Telaumbanua; Yupiter Mendrofa; Serniati Zebua; Aferiaman Telaumbanua (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze the effectiveness of social media strategies in increasing brand awareness of products at UD. Tanda Setia, Gunungsitoli City. The research employs a qualitative approach with data collected through in-depth interviews, observations, and documentation involving the business owner, marketing staff, and customers. The results indicate that social media platforms—particularly Facebook, Instagram, and TikTok - play a significant role in building communication between the company and consumers. The applied strategies include creating engaging content, maintaining posting consistency, actively interacting with users, and utilizing digital promotional features. The use of social media has proven effective in expanding market reach, strengthening brand image, and enhancing customer trust in the products. However, the study also identifies several obstacles, such as limited human resources for content management, lack of creative design variations, and suboptimal use of digital data analytics. Overall, the social media strategy implemented by UD. Tanda Setia is considered effective in increasing brand awareness, although improvements are still needed in content consistency and the development of more professional and targeted digital marketing strategies.